2018
DOI: 10.4103/jrms.jrms_928_17
|View full text |Cite
|
Sign up to set email alerts
|

The effect of orlistat and weight loss diet on plasma ghrelin and obestatin

Abstract: Background:The objective of this study was to evaluate the effect of weight loss with hypocaloric diet and orlistat treatment in addition to hypocaloric diet on gut-derived hormones ghrelin and obestatin.Materials and Methods:A total of 52, euglycemic and euthyroid, obese female patients were involved in the study. The patients were assigned to two groups: Group 1 (n = 26) received hypocaloric diet alone and Group 2 (n = 26) received orlistat in addition to hypocaloric diet for 12 weeks. Anthropometric measure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
1
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 31 publications
1
1
0
1
Order By: Relevance
“…Our results are in accordance with previous reported studies, which demonstrated no changes in the food intake after 12-week administration of orlistat in obese male rats [34,62]. However, other related studies reported increased appetite after orlistat consumption as shown by increased level of serum ghrelin (gut-derived hormone) in obese women (who received 120 mg orlistat, 3 times/day for 12 weeks) [63], reduced levels of plasma cholecystokinin (CCK) (for inducing fullness and reducing hunger), peptide YY (PYY) and glucagon-like peptide-1-(7-36)-amide (GLP-1) in healthy individuals (received single dose of 120 mg orlistat) [64]. These inconsistencies might be due to the differences in types of subject and doses of orlistat used, as well as the durations of the studies.…”
Section: Discussionsupporting
confidence: 93%
“…Our results are in accordance with previous reported studies, which demonstrated no changes in the food intake after 12-week administration of orlistat in obese male rats [34,62]. However, other related studies reported increased appetite after orlistat consumption as shown by increased level of serum ghrelin (gut-derived hormone) in obese women (who received 120 mg orlistat, 3 times/day for 12 weeks) [63], reduced levels of plasma cholecystokinin (CCK) (for inducing fullness and reducing hunger), peptide YY (PYY) and glucagon-like peptide-1-(7-36)-amide (GLP-1) in healthy individuals (received single dose of 120 mg orlistat) [64]. These inconsistencies might be due to the differences in types of subject and doses of orlistat used, as well as the durations of the studies.…”
Section: Discussionsupporting
confidence: 93%
“…Previous reports have shown conflicting results in this regard, indicating the lack of effect of diet-induced weight loss on the plasma ghrelin levels [44,45]. Pamuk et al observed a slight increase in ghrelin levels after an orlistat-induced weight loss [46]. However, as these previous works only evaluated one specific ghrelin measurement, comparisons should be made with caution.…”
Section: Discussionmentioning
confidence: 98%
“…La obesidad representa un problema de salud pública a nivel mundial debido a su asociación con enfermedades crónicas no transmisibles y reducción de la calidad y expectativa de vida (1,2) . La estrategia terapéutica reconocida es el tratamiento médico-nutricional, que incluye dietoterapia, fármacos y la cirugía bariátrica (3)(4)(5)(6)(7) . El tratamiento médico-nutricional, bajo un enfoque multidisciplinario, busca lograr un estilo de vida saludable en el paciente con obesidad.…”
Section: Introductionunclassified